The Role of The Taysir Manhaji Method in The Development of Islamic Economic Law in Indonesia Through DSN-MUI Fatwas - Musadad, Ahmad; Baihaqi; Nasik, Khoirun; Khazin, A. Mufti; Syaifudin, Mochamad (Universitas Muhammadiyah Surakarta, 2025)
This study examines the role of the taysir manhaji method in the development of Islamic economic law in Indonesia through the fatwas of the National Sharia Council–Majelis Ulama Indonesia (DSN-MUI). Taysir manhaji refers to a methodological approach that facilitates legal decision-making with ease and flexibility, allowing Islamic legal rulings to adapt to changing economic realities. By applying fiqh principles, DSN-MUI has issued fatwas addressing contemporary financial practices, including wadiah, mudarabah, currency exchange, and Islamic hedging. This research employs a qualitative approach, combining document analysis and interviews to explore the practical implementation of taysir manhaji in DSN-MUI fatwas. The findings reveal that this method serves as a bridge between classical fiqh and modern financial practices while upholding maqasid al-shari‘ah (the objectives of Islamic law). Its flexibility enables practical solutions, as exemplified by DSN-MUI fatwas No. 1, 5, 18, and 22, without compromising fundamental Islamic legal principles. The study underscores the taysir manhaji method's significant contribution to the evolution of Islamic economic law, demonstrating its ability to accommodate modern economic demands while preserving the integrity of shari‘ah principles. Furthermore, it highlights the necessity of adaptability in Islamic legal thought to address the complexities of the global economic landscape.